Culture-independent detection of vibrio cholerae and Escherichia coli using real time polymerase chain reaction. - Fegidero, Roselle Joyce Genoraga
Escherichia coli and Vibrio cholerae are two of the most common foodborne pathogens found in aquatic products and their detection is important in the movement of seafood locally and globally. There are many types of detection developed but culture-dependent methods, although time-consuming and laborious, are still considered as the gold standard in most countries. There are also numerous studies on pathogen detection using molecular technologies which are found to be more accurate and faster than culture methods. This study aims to design primers for Escherichia coli and Vibrio cholerae for culture-independent detection. Selectivity test through Real Time PCR was done for both bacteria alongside with other bacterial strains to validate the specificity of the designed primers. To support the results of the Real Time PCR, in silico analyses for E. coli and Vibrio cholerae were also conducted. Results of the Real Time PCR amplified the target uidA (β-glucuronidase) gene of E. coli and hylA (hemolysin) gene of Vibrio cholerae at the early cycles of the test. In this study, it can be deduced that the primers designed for the amplification of E. coli uidA gene and Vibrio cholerae hylA genes are suitable to detect these bacteria.